Sulphur-doped activated carbon as a metal-free catalyst for acetylene hydrochlorination. Issue 57 (18th September 2020) - Qi, Xueyan; Chen, Weifeng; Zhang, Jinli
Abstract : A series of sulfur-doped spherical activated carbon (SAC) catalysts were prepared with phenyl disulfide (C12 H10 S2 ) as a sulfur source for acetylene hydrochlorination. Abstract : A series of sulfur-doped spherical activated carbon (SAC) catalysts were prepared with phenyl disulfide (C12 H10 S2 ) as a sulfur source for acetylene hydrochlorination. The S-doped catalyst exhibits preferable catalytic performance compared to that of the blank carrier with the reaction conditions of GHSV of 90 h −1 and at 180 °C. The catalysts were characterized by N2 adsorption/desorption (BET), elemental analysis (EA), thermogravimetric analysis (TG), temperature-programmed desorption (TPD), Raman spectrum (Raman) and X-ray photoelectron spectroscopy (XPS). The results indicate that the presence of sulfur species is favorable to promote the ability of reactant adsorption and inhibit carbon deposition. In addition, the electronic and chemical properties of catalysts were investigated by density functional theory (DFT) simulation. It is illustrated that the introduction of sulfur species can not only change the spin density and charge density but also create more active sites on a carrier. The single sulfur doped carbon material catalysts were designed for the first time and the desirable results make it a green catalyst for the industrial application of acetylene hydrochlorination.